Boundary layer tripping on a transonic compressor profile - Joseph, A.; Piotrowicz, M.; Flaszynski, P.; Doerffer, P.; Kaczynski, P. (Archives of Mechanics, 2024)
The numerical and experimental investigation of boundary layer tripping using steps on the suction side of a transonic compressor rotor has been presented in this paper. The presented research corresponds to an EU project known as TFAST (Transition Location Effects on Shock Wave Boundary Layer Interaction). A representative single passage test section has been designed to investigate the SBLI (Shock wave Boundary Layer Interaction) effects on the rotor profile. The geometrical and inflow boundary conditions have been defined by the project partner RRD (Rolls- Royce Deutschland). Two locations of step (x/c = 0.16 and x/c = 0.02) were chosen upstream of the shock location to investigate the boundary layer tripping effects and are compared with configuration without tripping setup. The numerical simulations were carried out on the test section model using the steady-state Reynolds Averaged Navier–Stokes (RANS) model with Explicit Algebraic Reynolds Stress Model (EARSM) turbulence model with transition effects included. The chosen turbulence model could accurately predict the shock location on the suction side of the lower profile in the test section and had a good agreement with wall pressure measurements using pressure taps. A detailed shock structure was captured using the schlieren technique and compared for different tripping configurations. To estimate the effectiveness of the tripping setup losses have been estimated using LDA (Laser Doppler Anemometry) along the traverse downstream the blade passage. To understand the tripping effect on the boundary layer a detailed investigation has been carried out at ten selected traverse locations from leading edge to trailing edge of the rotor profile. Based on the experimental validation of the defined numerical model for tripping setup, a few more step heights were compared at selected tripping locations numerically. To analyse the effect of step heights, the isentropic Mach number and wall shear stress are compared with without tripping configuration. The wake and stagnation pressure losses downstream of the profile have been compared to investigate the sensitivity of location and geometrical definition of the boundary layer tripping setup on the aerodynamic losses.